KOMUNIKASI POLITIK DALAM PEMILIHAN KALEBUN DI DESA SANATENGAH KECAMATAN PASEAN KABUPATEN PAMEKASAN - Sudahri, Sudahri (MEDIAKOM : Jurnal Ilmu Komunikasi, 2018)
Pilkades as a venue for political consolidation at the village level provides an educating political education. Residents are openly confronted with prospective "Kalebun" (village heads). The interesting thing to study in the implementation of Pilkades is the stage of the campaign where each candidate "Kalebun" competes to introduce himself, give promises, approach the village community, and several other approaches through the communication process, both directly carried out by the candidates " Kalebun "or by the successful team. This study aims, among others: To describe the role of political communication carried out by "Kalebun" candidates in winning elections; the form of communication carried out; obstacles faced in political communication with villagers in an effort to win the election of the "Kalebun" and the response of the village community. This type of research uses a qualitative descriptive research method. The target of this research is the selected "Kalebun" candidates and "Kalebun" candidates who lose the following with their successful team and the community as voters. Data collection uses an interview or interview method and a purposive sampling method.Keywords: Political communication, "kelebun", village elections